A Text Recognizing Device For Visually Impaired (International Journal of Engineering and Computer Science, 2018)
In the present world visually impaired people use Braille lipi language to read the books, but those books are available only in particular places like library etc. It has become very difficult for the visually impaired peoples to come out into the real world. Braille cannot be used in every place like in the mobiles, supermarket, and news papers. Due to this it has become difficult for the visually impaired people to read the text. To overcome this difficulties faced by the visually impaired, finger reader with speech assistance is used to read any printed text from the mobiles, news papers etc. we are using the assistive technology in this device to provide the assistance for the visually impaired people